2020
DOI: 10.33140/jepr.02.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Brief, School-Based Bystander Bullying Intervention: A Pilot Study Conducted at an Ethnically-Blended, Low-Income School

Abstract: The purpose of this study was to adapt a brief, bystander bullying intervention to be culturally appropriate for ethnicallyblended schools in low-income communities and to assess the social validity of the adapted intervention. A mixed-methods design with sequential sampling was used to collect qualitative data from focus groups and quantitative survey data. The researchers used Consensual Qualitative Research to analyze qualitative data and chi square analyses and independent sample t-tests to analyzed qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…That is, we found no differences in the reduction of bullying victimization or bias-based bullying victimization between White students and students of color. Consistent with preliminary research indicating that the adapted STAC intervention is appropriate for both White and Hispanic students (Midgett et al, 2020, the results of this study suggest the culturally adapted STAC intervention is effective in reducing bullying victimization and bias-based bullying victimization for all students, not just students of one racial/ethnic background. At baseline, White students reported a significantly higher frequency of bullying victimization than students of color.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…That is, we found no differences in the reduction of bullying victimization or bias-based bullying victimization between White students and students of color. Consistent with preliminary research indicating that the adapted STAC intervention is appropriate for both White and Hispanic students (Midgett et al, 2020, the results of this study suggest the culturally adapted STAC intervention is effective in reducing bullying victimization and bias-based bullying victimization for all students, not just students of one racial/ethnic background. At baseline, White students reported a significantly higher frequency of bullying victimization than students of color.…”
Section: Discussionsupporting
confidence: 83%
“…Findings from two pilot studies support the cultural validity of the adapted STAC intervention for students attending ethnically blended middle schools in low-income communities (Midgett et al, 2020;Moran et al, 2020). The majority of students (85%) indicated that the adapted program was culturally relevant and that the language and examples reflected what they observe at school (Midgett et al, 2020).…”
Section: Cultural Adaptation Of Stacmentioning
confidence: 76%
See 1 more Smart Citation
“…Further, approximately 55% of students do nothing when they witness cyberbullying (Olenik-Shemesh et al, 2015). Passive bystander behavior has been linked to moral disengagement (Hymel et al, 2005), diffusion of responsibility (Bjärehed et al, 2020), low defender self-efficacy (Sjögren et al, 2020), and a lack of confidence (Midgett, Doumas, Moran, et al, 2020), knowledge, or skills to intervene (Forsberg et al, 2014;Hutchinson, 2012), and not knowing what to do (Bauman et al, 2020). These factors may play an even greater role in cyberbullying due to the lack of social-emotional cues (Knauf et al, 2018;Runions & Bak, 2015), physical distance (Knauf et al, 2018), and ease of disseminating communication via social networks (Runions & Bak, 2015).…”
Section: Witnessing Cyberbullying As a Bystandermentioning
confidence: 99%
“…For example, in face-to-face bullying, bystanders are usually present, whereas in the case of cyberbullying, the bystander may witness the bullying while it is occurring or after the fact (e.g., a message is forwarded to them) [11]. Further, passive bystander behavior has been linked to moral disengagement [29,30], diffusion of responsibility [31], and a lack of confidence [32], knowledge, or skills to intervene [23,33]. These factors may play an even greater role in cyberbullying due to the lack of social-emotional cues [34,35], physical distance, real or perceived anonymity [34], and ease of disseminating communication via social networks [35].…”
Section: Introductionmentioning
confidence: 99%